Tahapan-Tahapan dalam Merancang Modul Ajar PAI Berbasis Kurikulum Merdeka - Fahrur Rozy; Indah Widya Jaya Putri Nasution; Siti Halimah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The idea of ​​the curriculum, namely the newest independent curriculum, requires teachers to be able to implement it by making changes, both in terms of teaching and teacher administration. Talking about administration, there are still many teachers found in educational institutions who do not understand the process of making administration, especially teaching modules, which are a substitute for lesson plans that are prepared systematically and impressively to achieve the expected indicators of success. Therefore, the aim of this research is to find out the stages in the process of preparing independent curriculum-based teaching modules. This research uses library research which is analyzed using a descriptive analysis approach. The results of this research are that in compiling an open module you must pay attention to 3 components, namely; common components, core components, and attachments.